2020
DOI: 10.3847/1538-4357/ab7248
|View full text |Cite
|
Sign up to set email alerts
|

Lowly Polarized Light from a Highly Magnetized Jet of GRB 190114C

Abstract: We report multi-color optical imaging and polarimetry observations of the afterglow of the first TeVdetected gamma-ray burst, GRB 190114C, using the RINGO3 polarimeter on the 2-m autonomous robotic Liverpool Telescope. Observations begin 201 s after the onset of the GRB and continue until ∼ 7000 s post-burst. High temporal resolution (∆t 2.3 − 4.6 s) and dense sampling of the RINGO3 light curves reveal a chromatic break at t ∼ 400 − 500 s -with initial temporal decay α ∼ 1.5 flattening to α ∼ 1 post-break -whi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 116 publications
3
50
0
Order By: Relevance
“…MASTER Global Robotic Net was developed to study the key tasks of modern extreme energy astrophysics: to discover optical counterparts of gamma-ray bursts and to discover polarization of GRB prompt optical emission [24][25][26][27][28][29] ; to independently localize the sources of gravitational wave, detected by LIGO/Virgo 12,13 , to investigate high energy neutrino sources 30 , fast radio bursts sources [31][32][33][34] and other extreme processes in Universe. MASTER conducted optical observations that reveal strong evidence for high energy neutrino progenitor 30 .…”
Section: Monitoringmentioning
confidence: 99%
“…MASTER Global Robotic Net was developed to study the key tasks of modern extreme energy astrophysics: to discover optical counterparts of gamma-ray bursts and to discover polarization of GRB prompt optical emission [24][25][26][27][28][29] ; to independently localize the sources of gravitational wave, detected by LIGO/Virgo 12,13 , to investigate high energy neutrino sources 30 , fast radio bursts sources [31][32][33][34] and other extreme processes in Universe. MASTER conducted optical observations that reveal strong evidence for high energy neutrino progenitor 30 .…”
Section: Monitoringmentioning
confidence: 99%
“…Note that ref. 50 found chromatic evolution in their early RINGO3 data. However, this effect is small, which leads to some additional scatter around the first steep-to-shallow decay transition.…”
Section: Gev (Fermi-lat) Observationsmentioning
confidence: 98%
“…Optical Observations: Optical data have been gathered from refs. 27,50,51 as well as GCN data from refs. [52][53][54][55][56][57][58][59] .…”
Section: Gev (Fermi-lat) Observationsmentioning
confidence: 99%
“…For 6 events (GRB 080928, GRB 091018, GRB 091208B, GRB 110205A, GRB 121024A, and GRB 131030A), the optical observations reported the detection of intrinsic polarization 17,19,20,[54][55][56] . For GRB 190114C, Jordana-Mitjans et al (2020) 23 reported the detection of polarization induced by the dust in the host galaxy.…”
Section: Very Large Telescope Observationsmentioning
confidence: 99%